Neobarombiella, a diverse, newly described genus of Afrotropical Galerucinae (Coleoptera, Chrysomelidae) - Bolz, Helmut; Wagner, Thomas (Zootaxa, 2012)
Galerucinae with elongate basal metatarsi have traditionally been assigned to the “Monoleptites”. In recent studies itbecame clear that several species could not be placed in genera that have already been described. We here describe andredescribe species that form a distinct monophyletic group, defined by their external and genitalic characters, asNeobarombiella gen. n. This new genus is based on the examination of 3,554 specimens from continental Africa, andcontains 35 valid species and 36 new synonyms: Neobarombiella flavilabris (Weise, 1903) comb. n. (= Candezeaacutangula Weise, 1903 syn. n.; = Candezea vivida Weise, 1909 syn. n.; = Barombia benguelensis Laboissière, 1921 syn.n.; = Barombia gregaria Laboissière, 1931 syn. n.; = Barombiella bifasciata Laboissière, 1939 syn. n.; = Barombiellaclypeata Laboissière, 1940 syn. n.; = Barombiella ghesquierei Laboissière, 1940 syn. n.; = Barombiella trifasciata Laboissière, 1940 syn. n.; = Barombiella vicina Laboissière, 1940 syn. n.; = Barombiella wittei Laboissière, 1940 syn.n.); Neobarombiella nigrita (Jacoby, 1894) comb. n.; (= Candezea morio Jacoby, 1906 syn. n.); Neobarombiellapictipennis (Jacoby, 1894) comb. n.; Neobarombiella nigrocaerulea (Jacoby, 1897) comb. n. (= Candezea moliroensisJacoby, 1900 syn. n.; = Monolepta kwaiensis Weise, 1903 syn. n.; = Barombia ruficollis Laboissière, 1920 syn. n.; =Barombia ruficollis var. marginata Laboissière, 1920 syn. n.; = Barombia humeralis Laboissière, 1932 syn. n.; =Barombiella monardi Laboissière, 1939 syn. n.; = Monolepta (Candezea) nigeriae Bryant, 1940 syn. n.); Neobarombiellavariopennis (Jacoby, 1897) comb. n.; Neobarombiella punctatolineata (Jacoby, 1899) comb. n. (= Monolepta opulentaJacoby, 1903 syn. n.; = Barombia gibbosa Laboissière, 1920 syn. n.); Neobarombiella salisburiensis (Jacoby, 1899)comb. n.; Neobarombiella pygidialis (Jacoby, 1906) comb. n. (= Monolepta prasina Weise, 1907 syn. n.; = Monoleptaalutacea Weise, 1915; = Barombia truncata Laboissière, 1929 syn. n.); Neobarombiella mendica (Weise, 1909) comb. n.(= Monolepta pruni Bryant, 1937 syn. n., = Barombiella mimula Laboissière, 1939 syn. n.); Neobarombiella vittigera(Weise, 1912) comb. n. (= Barombia quadrilineata Laboissière, 1921 syn. n.); Neobarombiella punctata (Laboissière,1920) comb. n.; Neobarombiella flavicollis (Laboissière, 1923) comb. n. (= Barombiella piceobasalis Laboissière, 1940syn. n.); Neobarombiella suturalis (Laboissière, 1923) comb. n.; Neobarombiella senegalensis (Laboissière, 1923) comb.n. (= Barombiella leopoldi Laboissière, 1929, syn. n.; = Barombiella clathrata Laboissière, 1939 syn. n.; = Barombiellacostai Laboissière, 1939 syn. n.; = Barombia bicincta Laboissière, 1940 syn. n.; = Barombiella mutabilis Laboissière,1940 syn. n.; Barombiella pallida Laboissière, 1940 syn. n.; = Barombiella variabilis Laboissière, 1940 syn. n.; =Barombia basalis Laboissière, 1940, syn. n.); Neobarombiella pakhassana (Laboissière, 1931) comb. n. (= Monoleptagossypiperda, Bryant, 1947 syn. n.); Neobarombiella sculptipennis (Laboissière, 1939) comb. n. (= Barombiella striataLaboissière, 1939 syn. n.); Neobarombiella apicalis (Bryant, 1956) comb. n.; Neobarombiella bilineata (Bryant, 1958)comb. n.; Neobarombiella multistriata (Bryant, 1958) comb. n.; Barombia jobiti Laboissière, 1920 is here transferred toBonesioides [Bonesioides jobiti (Laboissière, 1920) comb. n.]. The following 16 species are newly described:Neobarombiella budongoensis sp. n., N. congoensis sp. n., N. cornuta sp. n., N. emma sp. n., N. fassbenderi sp. n., N.frohnorum sp. n., N. frontalis sp. n., N. grotefendi sp. n., N. lineata sp. n., N. medvedevi sp. n., N. naumanni sp. n., N.nigrosuturalis sp. n., N. reichartzi sp. n., N. spielbergi sp. n., N. susannae sp. n., and N. zambiae sp. n. Neobarombiella isdescribed in detail, redescriptions are provided for all valid species, and comprehensive descriptions of the new speciesinclude figures of both external and genitalic characters, and distribution maps. A key is provided to facilitate speciesidentification. An analysis of phylogenetic aspects is given in which characters of species in the genus Neobarombiella are compared to closely related genera.